(untitled) (Update Dental College Journal, 2024)
Background: Fluoride may not be available to some children in African countries due to the non-use of fluoride containing toothpaste, parental perception and awareness of the benefits of fluoride in caries prevention and non-availability of fluoride in community and school water. Fluoride may also not be affordable for children of low socio-economic status in remote areas, slums areas and rural areas. Topical and systemic sources of fluoride, like fluoride drops, fluoride gel,fluoride solution, fluoride mouthrinses, fluoride tablets, and fluoride lozenges, may not be available in resource-poor countries. Method: An electronic literature search in Google Scholar, African journals online, Science direct and Google was done in August , 2023 using the Population, Concept and Context framework. Search terms and keywords were combined by Boolean operators. Two independent investigators screened titles, abstracts and accessible full texts of publications on fluoride varnish use among African children. Results: Full text was screened using inclusion criteria. Three articles were included as they were assessed to meet the aim of the review. They were hospital based and school-based studies with comparative, prospective, interventional, and randomized clinical trial and cluster-randomized controlled community trials, respectively Conclusion: Fluoride varnish can be an intervention for underserved children with white spot carious lesion in remote areas, slums areas and rural areas, and for non-cavitated carious lesions in resource poor settings. It is simple to use with simple armamentarium, More studies from diverse ethnic population in African countries will fill the gaps in knowledge. Update Dent. Coll. j: 2024; 14(1):28-30